Participatory selection and ranking of farm-level sustainability indicators: Evidence from the horticulture production system of Eritrea - Haile, Bereket Tsehaye; Dougill, Andrew J.; Ramoelo, Abel (New Agenda: South African Journal of Social and Economic Policy, 2024)
Measuring agricultural sustainability requires operational definitions and customised indicators, which should ideally be tailored to each country’s context and reflect the full participation of key stakeholders. BEREKET HAILE, ANDREW DOUGILL and ABEL RAMOELO report on their study in which farmers, extension workers and experts collectively drew up a comprehensive list of indicators from relevant literature that can be used to inform researchers worldwide in selecting pragmatic indicators for assessing agricultural sustainability.